Performance of Sustainable Geopolymer Concrete Made of Different Alkaline Activators - Yasmin R. Hamed; Mostafa M. Keshta; Mohamed M. Yousry Elshikh; Ahmed A. Elshami; Mohamed H. S. Matthana; Osama Youssf (Infrastructures)
A major challenge in modern infrastructure is the excessive reliance on traditional Portland cement, which contributes significantly to environmental degradation and durability issues. This study addresses the need for sustainable and durable construction materials by investigating geopolymer concrete as an eco-friendly alternative, optimizing its mechanical and microstructural properties to enhance long-term performance in infrastructure applications. The performance of sustainable geopolymer concrete made with silica fume (SF) and fly ash (FA) and utilizing different alkaline activators (AAs) was examined in this study. The alkaline activators included sodium hydroxide (SH), potassium hydroxide (PH), and sodium silicate (SS) solutions. A total of twelve geopolymer concrete mixes were prepared and evaluated. The study considered several variables, including SF content (ranging from 10% to 100%), type of AA (SH+SS or PH+SS), AA concentration, and the AA to cementitious materials (AA/C) ratio. Workability, compressive strength, bending strength, tensile strength, and water absorption were among the mechanical characteristics of the concrete that were assessed, both in fresh and hardened states of the proposed concrete. The geopolymer concrete microstructure was also examined by performing X-ray diffraction (XRD), energy dispersive X-ray (EDX), and scanning electron microscopy (SEM) investigations on a few chosen mixes. The findings showed that when SF content was 10%, 20%, 30%, and 100% as a replacement of FA, the concrete slump rose by 10%, 15%, 15%, and 120%, respectively. However, the compressive strength was increased only with up to 20% SF. Geopolymer concrete with PH as the alkaline activator exhibited up to 13% lower compressive strength compared to SH. The geopolymer concrete microstructure was influenced by the presence of SF, leading to the formation of ettringite. Some FA particles that remained unreacted or were only partially reacted, along with voids, were observed. The findings from this study contribute to the development of sustainable geopolymer concrete, offering a promising solution for green structural applications.